2020
DOI: 10.1002/ece3.5816
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal structure of diversity and demographic dynamics along a successional gradient of tropical forests in southern Brazil

Abstract: Analysis of the structure, diversity, and demographic dynamics of tree assemblages in tropical forests is especially important in order to evaluate local and regional successional trajectories. We conducted a long‐term study to investigate how the structure, species richness, and diversity of secondary tropical forests change over time. Trees (DBH ≥ 5 cm) in the Atlantic Forest of southern Brazil were sampled twice during a 10‐year period (2007 and 2017) in six stands (1 ha each) that varied in age from their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 58 publications
1
14
0
2
Order By: Relevance
“…4G – 4I ). Dalmaso et al (2020) also found a net negative balance between recruitment and mortality leading to a reduction in plant density in advanced successional stages of a Brazilian Atlantic forest, likely reflecting intense competition. In our study, small plant density declined steadily after only 5 years of land abandonment ( Figs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…4G – 4I ). Dalmaso et al (2020) also found a net negative balance between recruitment and mortality leading to a reduction in plant density in advanced successional stages of a Brazilian Atlantic forest, likely reflecting intense competition. In our study, small plant density declined steadily after only 5 years of land abandonment ( Figs.…”
Section: Discussionmentioning
confidence: 85%
“…These authors attributed this peak mortality (and a concomitant decline in the dominance of pioneer species) to competition within this guild—rather than competition with the mature forest guild. Canopy closure and the structural recovery of vegetation along succession are expected to increase the influence of competition and density-dependent processes on plant dynamics ( Callaway, 1997 ; Bhaskar, Dawson & Balvanera, 2014 ; Sanaphre-Villanueva et al, 2017 ; Dalmaso et al, 2020 ). The higher mortality of large plants at the intermediate successional stage may thus be associated with competition and density-dependent processes ( Niinemets, 2010 ; Sanaphre-Villanueva et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, phylogenetic and taxonomic diversity were not significantly different between early successional ages, suggesting a failure in detecting phylogenetic diversity as a predictor for ecosystem function. Previous studies [3,11,13,56] argued that this failure may be caused by inappropriate study design when considering the species pool, experimental design, and analyses, such as using inappropriate phylogenies, skewed distributions of phylogenetic distances or the absence of sufficient niche space in experimental and observational venues [57].…”
Section: Discussionmentioning
confidence: 99%
“…The Vale do Ribeira Region has large biodiversity and there is also the estuary-lagoon complex Cananéia-Iguape, a region of rich biological diversity (SOS Mata Atlântica/ INPE 2018). Due to its important biodiversity, studies are needed to provide information on the degradation status of protected areas in this fragment of the Atlantic forest (Prado et al 2019, Dalmaso et al 2020. Currently, sand extraction in riverbeds is an industrial process that has been increasing in the Vale do Ribeira Region (SOS Mata Atlântica/ INPE 2018), and the industrial activity is called sand mining.…”
Section: Introductionmentioning
confidence: 99%